PENGGUNAAN PETA KONSEP DALAM PEMBELAJARAN STATISTIKA DASAR DI PROGRAM STUDI PENDIDIKAN MATEMATIKA FKIP UNIVERSITAS PGRI PALEMBANG - Rohana; Hartono, Yusuf; Purwoko (Mathematics Education Journal, 2009)
This research aims at describing how students’ understanding on statistical concepts upon using concept map is. Subjects in this research were students who took elementary statistics. Data were collected through observation and test, and were analyzed descriptively. The result shows that using concept map helps students improve their understanding on statistical concepts. DOI: 10.22342/jpm.3.2.331